Phosphorus harvesting from fresh human urine: A strategy of precisely recovering high-purity calcium phosphate and insights into the precipitation conversion mechanism. (1st December 2022) - Zhang, Bing; Tian, Shiyu; Wu, Deli
Highlights: A strategy of precisely harvesting P from fresh urine as calcium phosphate is proposed. The P recovery and product purity are precisely adjusted by regulating Ca/P ratio. The effects of urine composition and storage condition on P recovery are studied. The precipitation conversion mechanism is probed by thermodynamic model. Abstract: Phosphorus (P) harvesting from source-separated urine to optimize the overall nutrient loop is one of the most appealing benefits and is a global research interest in wastewater management and treatment. However, current P precipitation is mainly oriented to struvite, which is limited by the issues such as relatively low product purity and high cost of Mg source. Distinguished from previous conventional struvite precipitation, the strategy of precisely harvesting P from fresh human urine as high-purity calcium phosphate was first proposed in this study. This enhanced strategy can optimize P harvesting performance and product purity by simply regulating the consumption of calcium-based materials via model simulation and experimental validation. The thermodynamic model was constructed to probe the precipitation conversion mechanism, and visually predict the component and yield for products under various operating conditions. Batch experiments were conducted to investigate P recovery performance as a function of initial Mg 2+ concentration, initial pH level, as well as degree of urine hydrolysis. Moreover, the alternative dosing scheme with different calcium salts and alkali was presented, diversifying the options for efficient P recovery. The results showed that, from the perspective of acidic storage for fresh urine, P recovery can be boosted along with eliminating urine hydrolysis. In urine with an initial pH=2.0, P can be completely recovered and purity for calcium phosphate can be optimized to 100% within a Ca/P ratio range of 1.67–2.3. Overall, this work is of great significance for precisely and efficiently harvesting P from urine and provides an integrated strategy for P resource recovery from urine. Graphical abstract: Image, graphical abstract